Blended learning and online learning with project-based learning: Do they affect cognition and psycho-motor learning achievement in physical conditions? - Umar Umar; Ardo Okilanda; Mikkey Anggara Suganda; Pringgo Mardesia; Didi Suryadi; Dewi Wahyuni; Suciati Rahayu Widyastuti; Y Touvan Juni Samodra; Fajar Kurniawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background and the Aim of the Study. Online learning is only available in a limited capacity via the WhatsApp group. The WhatsApp group application is used to provide learning material which is often offered in the form of films obtained from YouTube, very brief explanations, and assignments. Therefore, special attention is needed in considering online learning methods so that learning objectives can be achieved. This study aims to determine the effect of blended learning and project-based learning on the cognitive and psychomotor capacities of Padang State University students. Material and Methods. This study uses a quantitative approach. This research was conducted at Padang State University with third-semester students enrolled in the 2022 physical condition course. A total of 80 students in the third semester of the physical condition course in 2022 were used as a sample. Data on learning outcomes and psychomotor learning achievements were obtained using an observation sheet of e-test skills in the form of video conferencing learning. Data analysis techniques in this study were assisted by using the SPSS application. Results. Cognitive learning outcomes of students who are taught with the project-based learning model reach an average of 72.3. This average is greater than the average of students studying the blended learning (BL) model, namely 63.5. Students who were taught using the project-based learning (PjBL) model had an average psychomotor learning result of 81.3 greater than students who were taught with the blended learning model which had an average of 76.3. Conclusions. The results show that blended learning and online learning models with project-based learning have a major impact on cognitive and psychomotor outcomes in learning achievements under physical settings. Testing the model on variables other than physical health can be used for additional study, and it is important to look at other variables that affect students' progress in cognitive and psychomotor learning.